Political ideologies, fourth edition : an introduction - Heywood, Andrew ([S.l.] : Palgrave Macmillan, 2007)
This revised and updated fourth edition of the leading text on political ideologies contains a new chapter on multiculturalism, consideration of the changing nature of ideological discourse, including the transition from "traditional" to "new" ideologies, and coverage of the impact on the major ideolgoical traditions of developments such as globalization and the "war on terror".
Keywords: Ideology; Political science; Right and left (Political science)